The contribution of administrative information systems in providing services to trainees at the Institute of Public Administration in Riyadh, Kingdom of Saudi Arabia - Alakeel, Ahmed Saud (Journal of Economic, Administrative and Legal Sciences, 2024)
The problem of the study is to identify administrative information systems and their role in providing services to trainees from government agencies in the city of Riyadh. The scientific importance of this study highlights the great development that management information systems have brought about in all aspects of life, and in the field of administrative development in particular. Most organizations have become dependent on management information systems and computer systems, where the importance of research lies in the inability of traditional methods to Providing appropriate information to trainees in the appropriate way to improve the service. The study aims to identify the reality of the impact of the use of management information systems at the Institute of Public Administration in Riyadh, the level of services provided to trainees from the Institute of Public Administration in Riyadh, and the extent to which management information systems contribute to improving and developing services for trainees, and to achieving the goals , The descriptive method was used, and to collect data, random sampling was used on a sample of (384) employees of government agencies benefiting from training services at the Institute of Public Administration in Riyadh. The study concluded that the members of the study sample agreed to a large degree on the reality of management information systems at the Institute of Public Administration. In Riyadh, the study sample members also agree with the high level of services provided to trainees at the Institute of Public Administration in Riyadh. And the extent to which management information systems contribute to improving and developing services for trainees. The study also found that the institute’s website provides information about the detailed objectives of the training programs according to job title, in a way that meets inquiries in this aspect by trainees and works to facilitate and streamline the process of communication with the institute’s website management from Before the trainees.
Keywords: Management Information Systems; Institute of Public Administration; Trainee Services; Kingdom of Saudi Arabia